JHEA, Volume 19, n°1, 2021 - Full Issue - Journal System, (Journal of Higher Education in Africa, 2022)
Contents Enhancing the Digital Transformation of African Universities: COVID-19 as Accelerator Paul Tiyambe Zeleza & Paul Mzee Okanda............................. 1 Competencies and Proficiencies in Special Education: The Case of Ethiopian Universities Workneh E. Woldehana & Damtew Teferra......................29 Teaching Styles of Educators in Higher Education in Eritrea: Teacher-centred or Student-centred? Ali Suleman Abdella & Aslam Fataar.............................45 Comparing Pedagogy in Kenya’s Public Universities: The Roles of University Managers Susan M. Kilonzo, Kennedy Onkware, Pamella A. Oloo & Simon G. Omare.............................63 Information Communication Technology (ICT) Utilisation and Associated Barriers in Teaching among Middle-level Academics in Nigerian Universities John Lekan Oyefara, Pius Adejoh, Waziri B. Adisa, Khadeejah A. Abdulsalam & Tunde Alabi ......................95 Les imaginaires populaires de la femme âgée face aux accusations de sorcellerie en République Centrafricaine : une perspective genrée Narcisse Landry Kevis Kossi.........................121 Politique de financement et gouvernance des universités publiques Sénégalaises : vers un nouveau paradigme ? Melyan Mendy..................................141 Existe-t-il un effet genre dans les performances académiques des étudiants dans les facultés des sciences économiques et de gestion au Cameroun ? Cas de la FSEG de l’Université de Yaoundé II Etienne Atala.......................................171